Phylogeny of Transferable Oxazolidinone Resistance Genes and Homologs - Gábor Kardos; Levente Laczkó; Eszter Kaszab; Bálint Timmer; Krisztina Szarka; Eszter Prépost; Krisztián Bányai (MDPI AG, 2024)
Oxazolidinone resistance, especially transmissible resistance, is a major public health concern, and the origin of this resistance mechanism is not yet resolved. This study aims to delve into the phylogenetic origin of the transmissible oxazolidinone resistance mechanisms conferring cross-resistance to other drugs of human and veterinary importance. The amino acid sequences of the five cfr ribosomal methylases and optrA and poxtA were used as queries in searches against 219,549 bacterial proteomes in the NCBI RefSeq database. Hits with >40% amino acid identity and >80% query coverage were aligned, and phylogenetic trees were reconstructed. All five cfr genes yielded highly similar trees, with rlmN housekeeping ribosomal methylases located basal to the sister groups of S-adenosyl-methionine-dependent methyltransferases from various Deltaproteobacteria and Actinomycetia, including antibiotic-producing Streptomyces species, and the monophyletic group of cfr genes. The basal branches of the latter contained paenibacilli and other soil bacteria; they then could be split into the clades [cfr(C):cfr(E)] and [[cfr:cfr(B)]:cfr(D)], always with different Bacillaceae in their stems. Lachnospiraceae were encountered in the basal branches of both optrA and poxtA trees. The ultimate origin of the cfr genes is the rlmN housekeeping ribosomal methylases, which evolved into a suicide-avoiding methylase in antibiotic producers; a soil organism (Lachnospiraceae, Paenibacilli) probably acted as a transfer organism into pathogenic bacteria. In the case of optrA, the porcine pathogenic Streptococcus suis was present in all branches, while the proteins closest to poxtA originated from Clostridia.